2022
DOI: 10.1101/2022.10.20.22281302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR/Cas12a assisted specific detection of monkeypox virus

Abstract: ObjectiveTo identify monkeypox-specific sequence and distinguish it from related orthopoxviruses followed by development of a CRISPR-Cas12a-based, specific and sensitive detection of monkeypox virus.MethodsA common detection mixture (CDM) was constituted comprising of CRISPR RNAs (crRNAs) for general orthopoxviruses and monkeypox virus-specific targets along with LbCas12a and fluorescent reporter. Recombinase polymerase amplification (RPA) of target loci was carried out followed by detection using the CRISPR-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In response to the current outbreak, CRISPR-based systems have been developed for MPXV diagnostics. 122 , 123 In one of the first detection methods, Sui and co-workers developed a CRISPR system that was able to detect the MPXV DNA by using fluorescence readout. 122 In this study, the authors found that the FAM fluorescent signal was detectable in 2 min and a strong signal was achieved within 10 min, indicating that the system has potential to apply in the field.…”
Section: Laboratory-based Diagnosis Of Mpoxmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the current outbreak, CRISPR-based systems have been developed for MPXV diagnostics. 122 , 123 In one of the first detection methods, Sui and co-workers developed a CRISPR system that was able to detect the MPXV DNA by using fluorescence readout. 122 In this study, the authors found that the FAM fluorescent signal was detectable in 2 min and a strong signal was achieved within 10 min, indicating that the system has potential to apply in the field.…”
Section: Laboratory-based Diagnosis Of Mpoxmentioning
confidence: 99%
“… 122 In another similar report, Singh and co-workers designed a CRISPR-Cas12a-based system to detect MPXV, achieving a high sensitivity and specificity to detect synthetic DNA. 123 Despite these promising findings, CRISPR/Cas-based diagnostic methods are not currently used in reference laboratories and need further implementation.…”
Section: Laboratory-based Diagnosis Of Mpoxmentioning
confidence: 99%
“…Until now, there are some monkeypox diagnostic methods that have been used for diagnosing the infections. Some of these techniques are polymerase chain reaction, , virus culture-based diagnosis, protein Cas-based diagnosis, , loop-mediated isothermal amplification, , enzyme-linked immunosorbent assay, , and recombinase polymerase amplification assay. ,, Considering the point-of-care (POC) nature of rapid tests, antibody-based immunoassays seem to be stronger diagnostic tool candidates for MPXV detection. However, due to the antigen context of Orthopoxvirus genomes, most human samples become cross-reactive, and this situation makes it impossible to differentiate different kinds of Orthopoxvirus viruses. …”
Section: Introductionmentioning
confidence: 99%